Analysis of Marine Debris Distribution Through Sort Transport Clean in the Coastal Waters of Ternate City - Yumima Sinyo; Ningsih Saibi; Deasy Liestianty; Dira Ayu Annisa (Universitas Khairun, 2024)
Marine pollution, originating from land-based sources and intentional dumping at sea, is a significant hazard to marine life and health. Plastic pollution, which constitutes about 85% of marine debris, causes severe damage to marine ecosystems and species, causing disruptions in marine activities and deteriorating seawater quality. This research aims to see the distribution of marine debris in the coastal waters of Ternate city. The method used in this research is purposive sampling technique through observation to obtain the composition of marine debris, the rate of increase of marine debris with 3 criteria, namely the presence of river mouths, community activities such as ecotourism activities and piles of garbage produced by fishermen. The data obtained was then analyzed by visually observing and recording. The result of this study is the discovery of organic and inorganic waste. The percentage density of organic waste is 13% while inorganic waste is 87%. This shows that inorganic waste is generated the most. Inorganic waste in the form of plastic, cloth, glass, steroform and aluminum is produced by human activities visiting the coast. The organic waste found is wood and fruit peels.